Effect of an experimental paste with hydroxyapatite nanoparticles and fluoride on dental demineralization and remineralization in situ - Souza, Beatriz Martines de (2015)
This study evaluated the potential of an experimental paste containing nano- HA/fluoride on the reduction of dental demineralization and on the increase of dental remineralization in situ. Thirteen subjects took part in this crossover and double-blind study performed in 4 phases (14 days each). Four sound (S) and 4 predemineralized (WS) specimens were worn intraorally at each phase corresponded to the following treatments: Nanop plus (10% hydroxyapatite + 900 ppm F), MI Paste Plus (CPP-ACP + 900 ppm F), F (900 ppm F) and placebo (without active ingredients). For that, 480 specimens (240 enamel and 240 dentin) were selected by using surface microhardness; half of the samples were subjected to demineralization (WS, demineralizing solution at pH 5, for 6 and 7 days, respectively) and the other half remained sound (S). S specimens were protected from disturbance by using plastic mesh to allow biofilm accumulation; while on WS no biofilm accumulation was allowed to facilitate remineralization. S specimens were further exposed to severe cariogenic challenge (20% sucrose, 8x5min/day for enamel and 4x5min/day for dentin). The treatments were done 2x4 min/day, extraorally. The de-remineralization was quantified by transversal microradiography. The data were statistically analyzed using Repeated-Measures ANOVA followed by Tukeys test (p<0.05). In respect to dentin demineralization, Nanop Plus had the best effect on the reduction of Z (%minxm), while all treatments were similarly able to reduce to the lesion depth (m) compared with placebo: Nanop Plus (780.5 ± 212.0, 98.8 ± 26.2); MI Paste Plus (876.0 ± 268.4; 95.7 ± 30.5); F (900.5 ± 236.3; 96.0 ± 26.1); Placebo (1188.2 ± 502.5; 142.7 ± 28.0), respectively (p<0.05). For enamel demineralization, no treatment was able to reduce Z and lesion depth compared to placebo: Nanop Plus (1000.9 ± 249.5, 45.0 ± 15.3); MI Paste Plus (883.6 ± 431.7; 60.7 ± 26.4); F (985.5 ± 313.4, 53.4 ± 21.1); Placebo (1369.6 ± 988.3, 57.2 ± 30.6), respectively. In respect to dentin remineralization, all treatments were similarly able to improve mineral uptake (Z) compared to placebo: Nanop Plus (910.1 ± 328.8); MI Paste Plus (964.2 ± 446.4); F (902.1 ± 606.8); Placebo (337.9 ± 408.2) (p<0.05). For enamel, only the Nanop Plus and F were effective in increasing mineral uptake (Z) compared to placebo: Nanop Plus (549.9 ± 405.4); MI Paste Plus (370.8 ± 230.6); F (555.5 ± 264.1); Placebo (200.4 ± 186.8) (p<0.05). Nanop Plus is more effective than MI Paste Plus on the reduction of dentin demineralization and the increase of enamel remineralization. No treatments were able to reduce enamel demineralization, while for dentin remineralization all treatments were effective.